Research Associates Program: Expanding clinical research productivity with undergraduate students. (7th September 2017) - Hoonpongsimanont, Wirachin; Sahota, Preet K; Ng, Nathan N; Farooqui, Maryam J; Chakravarthy, Bharath; Patel, Bhakti; Lotfipour, Shahram
Objectives: Clinical research is often time-consuming and difficult to conduct in busy academic institutions. Previous studies have proposed methods to integrate undergraduate students as a means to increase research productivity. The authors aimed to describe the possibility to enhance emergency department research productivity at an academic emergency department in the United States, using undergraduate students in an Emergency Medicine Research Associates Program. Methods: The authors described the Emergency Medicine Research Associates Program curriculum and its implementation. We also conducted a retrospective study at a university-based emergency department from January 2005 to December 2014 to demonstrate the benefit of having an established Emergency Medicine Research Associates Program. The primary outcomes were number of Emergency Medicine Research Associates Program–related studies, number of enrolled patients, extramural/intramural funding, abstract presentations, and peer-reviewed publications. The authors analyzed the data using descriptive statistics. Results: Over the 10-year period, 110 Emergency Medicine Research Associates Program–assisted research studies were conducted, with research associates enrolling 46, 219 patients. These studies yielded a total of 31 peer-reviewed publications and 77 abstract presentations (13 international, 27 national, 37 state/regional). The Emergency Medicine Research Associates Program–related studies were used as pilot studies to obtain US1, 751, 036 in extramural grant funding and US31, 047 in intramural grant funding. Conclusion: The implementation of Emergency Medicine Research Associates Program can enhance emergency department clinical research productivity, and the inclusion of supplemental academic programs enhanced the undergraduate students' research experience.